Physical Layer Security in Wireless Cooperative Networks - Wang, Li.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book provides a comprehensive overview for physical layer security in wireless cooperative networks, including fundamental concepts, typical solutions, and some recent achievements. It investigates the secrecy performance with respect to time reversal transmission and multi-antenna spatial modulation techniques. Both of which are proposed as effective physical layer processing schemes in wireless multipath channel environment. Resource allocation strategies to enhance secrecy performance in D2D communications are also discussed in this book. It contributes to formulating user social behaviors and utilizing social characteristics to improve the secrecy performance in wireless cooperative networks. This book not only analyzes the secrecy enhancement with certain techniques, but also pursues to find the relationships or tradeoffs among the secrecy performance, energy consumption, channel conditions, and other essential factors in wireless communications. This book targets researchers and professionals specializing in electronic engineering, computer science,wireless communications and networks. Advanced level students in electrical engineering and computer science will also find this book useful as a secondary text.
1 Introduction -- 2 Existing Techniques in Physical Layer Security -- 3 Secrecy Analysis with Time-Reversal Technique in Distributed Transmission System -- 4 Spatial Modulation in Physical Layer Security -- 5 Cooperative Security in D2D Communications -- 6 Summary.
Keywords: Telecommunication; Data protection; Computer networks .; Communications Engineering, Networks; Data and Information Security; Computer Communication Networks